Land Legal Policy Registration of Customary Rights: Islamic Land Law Perspective - Absori; Ach. Nurul Luthfi; Istani (Journal of Transcendental Law, 2025)
Article 28H paragraph (4) of the 1945 Constitution of Indonesia guarantees citizens the right to private property, including land, which cannot be taken arbitrarily. This study aims to: (1) describe current land titling policies; and (2) explain the policy on registering customary land rights. The research uses a normative, qualitative doctrinal approach. In Islamic land law, land is considered the property of Allah SWT, with humans granted authority to manage it in accordance with sharia. Thus, land management should adhere to divine, not human, laws. Indonesia’s current land certification policy is based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 12 of 2017, which governs the Acceleration of Complete Systematic Land Registration (PTSL). This program targets certification of 126 million land parcels by 2025. Land registration contributes to community welfare by offering legal certainty and protecting property rights. However, Government Regulation No. 27/1999 does not recognize customary (ulayat) land as eligible for certification, despite the constitutional mandate and the Basic Agrarian Law (UUPA) to protect such lands. To resolve this, the government can issue Customary Land Certificates through Regional Regulations as part of the Customary Land Registration process, ensuring legal recognition and protection of customary community land rights.